Belis in Traditional Marriage Traditions in Sikka: An Accounting Perspective - Gracela Pinkan Antou; Maria Mediatrix Ratna Sari (Fakultas Ekonomi dan Bisnis Universitas Udayana, 2025)
Belis actually aims to elevate women's status. However, it becomes a problem because the demand for belis seems to be burdensome for men. The aim of the study was to find out the process of identifying, measuring and communicating belis for women in Sikka from an accounting perspective, using ethnographic studies and descriptive qualitative methods, with 4 respondents and purposive sampling techniques using the data analysis model of Spradley (1979). In identification, it is found that the stages of buying are equated with fixed costs and variable costs. It can be seen that the involvement of the parties is equivalent to the 3 levels of company management. The findings show that belis is not looking for profit and there is no provision for the value to be brought. Belis is given on the ability of men as a reward and is measured using fair value where the cost is adjusted to market prices that are beneficial in the future. Belis recording is not used as evidence of accounts payable but rather as a symbol. In the belis tradition, communication is formed from direct agreement. This research requires analysis in making decisions. This research can be used as information for couples who want to get married, especially men in preparing belis and add to the reader's insight about traditional marriages from an accounting perspective.